Studying Political Theory Subjects Using Flipped Classroom Model - Assessment from Gen-Z Students (Journal of Contemporary Educational Policies and Practices, 2022)
Political Theory subjects play critical roles in Vietnam’s society in the current context of the 4th Industrial Revolution, globalization and information explosion. Particularly, the recent decade has welcomed the emergence of a new generation of university students - generation Z, with distinctive characteristics compared to previous generations, that is: activeness, creativity, adaptability, and familiarity with technology. Therefore, it is inevitable to innovate the methods of teaching with Political Theory subjects to keep pace with these developments in education. The flipped classroom model has so far been implemented in teaching the Political Theory Subjects in several universities. This study is designed based on the flipped classroom model, employing questionnaires with a 5-point Likert scale for 648 students at Hanoi National University of Education. The data collected was analyzed with SPSS 20.0 software. Open-ended questions are also included in the questionnaire to gather a variety of personal viewpoints. Besides, the research method of interview was applied with 30 students. The study aims to clarify gen-Z students’ judgment of using the flipped classroom model in teaching Political Theory subjects. Furthermore, the author sheds light on the suitability and effectiveness of the very teaching model as a basis for its future application.